Salivary Changes in Patients Hospitalized for Complications of HIV Infection/AIDS: A Study Using Inductively Coupled Plasma Optical Emission Spectrometry - Klamas, Vanessa Cavassin; Ventura, Mateus Anhaia; Baika, Loana Mara; Kamei, Adryano Arana; Naka, Jhonatan Yukio; Chaiben, Cassiano Lima; Grassi, Marco Tadeu; de Lima, Antonio Adilson Soares (Journal of Dentistry Indonesia, 2023)
Objective: The aim of this study was to analyze the salivary flow and levels of major salivary ions of HIV-infected individuals. Methods: One hundred and two participants (18 - 74 years of age) were divided into two groups (51 HIV - infected patients and 51 controls) and had a saliva sample collected. Salivary flow rate was measured gravimetrically. Levels of salivary sodium, potassium, magnesium, calcium and phosphorus were analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES). Results: The mean salivary flow of subjects with HIV infection was significantly higher when compared to controls (Case group = 1.0 mL/min + 0.63 / Control group = 0.7 mL/min + 0.46; p = 0.012). Sodium, potassium and calcium levels were significantly higher in the saliva of the patients HIV infection when compared to controls. There was no difference between the salivary levels of magnesium and phosphorus ions between groups. Conclusion: Based on these findings, it can be concluded that individuals with HIV / AIDS develop salivary changes. Thus, these patients need a greater attention to oral health by dentists, since salivary changes induced by the disease can lead to impairment in the oral condition.